Análise ergonômica de instrumentos líticos pré-históricos brasileiros: uma contribuição para a história da ergonomia - Menin, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Ergonomics is a science, if not the only one, with the exact date of its appearance - July 12, 1949. In Brazil, this science is just a little more than 30 years of age. The history of Ergonomics - i.e. the entire period following its date of birth - has been extensively studied in Brazil and worldwide. But what precedes this history, which we may call the pre-history of Ergonomics, has been little debated until now. For many authors, the beginning of this relates to the creation of the first Man-made tools, i.e. when primitive man feels the need to adapt tools to facilitate their everyday tasks. Thus, Archeology - the science that studies Man's past through material remains of their activities, can be an important tool for invesetigating this hypothesis and to understand the criteria that man already sought like comfort, safety and ease of construction of their tools. The aim of this thesis is the analysis of chipped stone tools developed by prehistoric men, specially, evaluating the grips/handles of their tools, being possible to provide data and information to contextualize the history of Ergonomics in Brazil. Lithic artifacts from the CEMAARQ of the UNESP of Presidente Prudente (SP), from the Museum the Archaeology and Paleontology of Araraquara (SP) and from the Municipal Museum of Jahu (SP) were used as objects os study. The archaeological pieces chosen were molded using a mixture of polyurethane liquid rubber (silicone mold). With the aid of the molds, the archaeological tools were reproduced accurately - regarding weight and color - in polyester resin and an addition of sand and micro spheres of iron. After the reproduction of the pieces, the grips/handles were analyzed. The method used for assessing the type of grip was the use of gloves equipped with FSRs sensors, which record the loads during the simulation of possible activities performed with lithic tools

A ergonomia é uma das ciências, se não a única, com data exata de seu nascimento - 12 de julho de 1949. No Brasil esta ciência tem pouco mais de 30 anos. A história da Ergonomia, ou seja, todo o período posterior à sua data de nascimento vem sendo muito estudada no Brasil e no mundo. Porém o que precede essa história, o que podemos chamar de pré-história da Ergonomia, até hoje foi pouco debatida. Para vários autores o início desta está relacionado à criação das primeiras ferramentas pelo Homem, ou seja, quando o homem primitivo sente a necessidade de adaptar instrumentos para facilitar suas tarefas cotidianas. Assim, a Arqueologia - ciência que estuda do passado do homem através de restos materiais de suas atividades, pode ser uma importante ferramenta para investigação desta hipótese e para a compreensão dos critérios que o homem já busca de conforto, segurança e facilidade na construção de suas ferramentas. O objetivo desta tese é a análise de ferramentas de pedra lascada desenvolvidas pelos Homens pré-históricos, avaliando principalmente as pega/empunhaduras de seus instrumentos, sendo possível apresentar dados e informações para a contextualização da história da ergonomia no Brasil. Foram utilizados como objetos de estudo artefatos líticos do CEMAARQ da UNESP de Presidente Prudente (SP), do Museu de Arqueologia e Paleontologia de Araraquara (SP) e do Museu Municipal de Jahu (SP). As peças arqueológicas escolhidas foram moldadas com mistura de borracha líquida de poliuretano, molde de silicone. Com o auxílio dos moldes os instrumentos arqueológicos foram reproduzidos - de maneira fiel com relação ao peso e cor - em resina de poliéster e cargas (areia e micro esferas de ferro fundido). Após a reprodução, as pegas/empunhaduras foram analisadas. O método utilizado para a avaliação do tipo de preensão foi o emprego de luvas dotadas de sensores FSRs que registram as cargas durante a...
Keywords: Ergonomia; Implementos líticos; Arqueologia; Human engineering